2019
DOI: 10.1155/2019/3174768
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Primary Bone Lymphoma of the Hip: A Case Report and Review of the Literature

Abstract: Introduction. Primary bone lymphoma (PBL) is a rare bone malignancy which may present with atraumatic pain, swelling, or pathological fracture. Whilst the femur is the most commonly affected site, any bone may be involved. PBL should be distinguished from other bone lesions to determine clinical management. Case Report. We report the case of an 89-year-old gentleman who presented to the local emergency department with atraumatic hip pain and inability to weight-bear. Multimodal imaging showed evidence of a tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In addition, a recent prospective study has confirmed that complete surgical resection is beneficial for patients with early-stage DLBCL because complete resection minimizes tumor mass and induces a positive impact on outcome (18). As previously reported, a patient with DLBCL in the hip achieved a favorable outcome by multimodal therapy of R-CHOP chemotherapy, radiotherapy, and surgical management (19). Thus, complete resection could be worth considering when the affected area can be removed without jeopardy.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, a recent prospective study has confirmed that complete surgical resection is beneficial for patients with early-stage DLBCL because complete resection minimizes tumor mass and induces a positive impact on outcome (18). As previously reported, a patient with DLBCL in the hip achieved a favorable outcome by multimodal therapy of R-CHOP chemotherapy, radiotherapy, and surgical management (19). Thus, complete resection could be worth considering when the affected area can be removed without jeopardy.…”
Section: Discussionmentioning
confidence: 68%